2010
DOI: 10.1107/s0909049510028451
|View full text |Cite
|
Sign up to set email alerts
|

A new technique to examine individual pollutant particle and fibre deposition and transit behaviour in live mouse trachea

Abstract: During respiration, particles suspended in the air are inhaled and unless cleared by airway defences they can remain and affect lung health. Their size precludes the use of standard imaging modalities so we have developed synchrotron phase-contrast X-ray imaging (PCXI) methods to non-invasively monitor the behaviour of individual particles in live mouse airways. In this study we used these techniques to examine post-deposition particle behaviour in the trachea. PCXI was used to monitor the deposition and subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…This technique can be used in vivo in live anaesthetised mice456. By comparison, conventional in vivo MCT measurement methods rely on measuring bulk particle clearance from the airways78910, are unable to track the motion of individual micron sized deposited particles with high spatial or temporal resolution, and cannot be used to assess spatial or temporal variations in MCT homogeneity within the airways.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…This technique can be used in vivo in live anaesthetised mice456. By comparison, conventional in vivo MCT measurement methods rely on measuring bulk particle clearance from the airways78910, are unable to track the motion of individual micron sized deposited particles with high spatial or temporal resolution, and cannot be used to assess spatial or temporal variations in MCT homogeneity within the airways.…”
mentioning
confidence: 99%
“…Provided the X-ray beam is spatially coherent, increasing the sample to detector distance131415 enhances tissue boundaries due to the phase changes that are induced by differences in the tissue X-ray refractive indices. We have reported on the benefits of PCXI for non-invasive airspace imaging in small animals16, for non-invasive particulate detection in live mouse airways45617, and for the visualisation and assessment of surrogate fluid dosing regimes for airway gene therapy treatments in live mice1819. Our previous studies also examined the MCT behaviour of a range of common pollutant particles delivered to the airways in either a saline carrier fluid56 or as a dry powder4.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The boundaries between tissue and air are enhanced by the phase changes in the incident X-ray wave induced by their differences in X-ray refractive index. 6,7 We have described the advantages of PCXI for airway surface imaging in small animals, 9,10 for monitoring the post-deposition behavior of particulates on live mouse nasal and tracheal airways, 11,12 and for non-invasively tracking how a fluid bolus-typical of that used in airway gene-therapy dosing-moves through the airways of live and intact small animals. 13 Our previous fluid dosing study 13 showed the immediate fate of fluids instilled into the nose and trachea of live anesthetized mice, demonstrating that the overall distribution of the dose, the effectiveness of the delivery method, and the persistence of the delivered dose can now be visualized.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 We have previously demonstrated the advantages of PCXI for small animal airway surface imaging 10,11 and for monitoring the post-deposition behavior of particulates on live mouse nasal and tracheal airways. 12,13 In this study we used PCXI to precisely and noninvasively track how introduced fluids, typical of those used in airway dosing, move through the airways of live and intact small animals.…”
Section: Introductionmentioning
confidence: 99%